Pengaruh Inflasi, GDP, CAR, dan FDR Terhadap Non Performing Financing (NPF) Bank Umum Syariah : Doni Hari Prastyo, Saiful Anwar - Saiful Anwar; Doni Hari Prastyo Sukiyat (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
The purpose of this study was to determine the effect of inflation, Gross Domestic Product (GDP), Capital Adequacy Ratio (CAR), and Financing to Deposit Ratio (FDR) on Non-Performing Financing (NPF). This research uses quantitative research using linear regression analysis of panel data. This study uses panel data on Islamic Commercial Banks (BUS) for the 2015-2019 period. The data processing used is Eviews 9. The sampling method used is purposive sampling, which uses several criteria so that there are 11 Islamic Commercial Banks as research samples. The results of this study indicate that inflation, GDP, and FDR variables have a positive influence on NPF, while the variable BOPO has a negative effect on NPF.